Molecular cloning, expression analysis, and functional characterization of an interleukin-15 like gene in common carp (Cyprinus carpio L.) - Jiang, Xinyu; Wang, Xiaoyu; Gao, Mengjie; Li, Xudong; Ding, Yi; Song, Yunjie; Xiao, Hehe; Kong, Xianghui (Frontiers in Immunology, 2024)
Interleukin-15 (IL-15) is a crucial cytokine involved in immune system regulation, which is produced by various cell types, including dendritic cells, monocytes, and macrophages. IL-15 plays a key role in the proliferation and activation of natural killer (NK) cells, CD8+ T cells, and memory CD8+ T cells, supporting their survival and enhancing their effector functions. Although IL-15 homologues in fish have been identified, their functions remain poorly understood. In this study, we cloned and investigated the bioactivities of an IL-15 homologue, referred to as IL-15 like (CcIL-15L), in common carp (Cyprinus carpio L.). An expression pattern analysis revealed that CcIL-15L was constitutively expressed in all examined tissues of healthy common carp, with the highest expression level observed in the intestine. Additionally, CcIL-15L expression was significantly up-regulated in the head kidney, spleen, gills, and intestine following Aeromonas hydrophila infection. In vitro, the recombinant protein CcIL-15L can significantly up-regulated the gene expression levels of pro-inflammatory cytokines (IL-1β, IL-6, IFN-γ, and TNF-α) and NK cell activation (perforin and Eomesa). We constructed a 3×FLAG eukaryotic expression vector and successfully expressed it in common carp by intramuscular injection. Additionally, the heterologous CcIL-15L protein was successfully overexpressed in vivo, and immune-related genes including CD4-1, CD8β2, TNF-α, and IgM showed significant induction in the head kidney and spleen. Furthermore, CcIL-15L overexpression reduced the bacterial loads after 24 h post-A. hydrophila infection in the liver, spleen, and kidney. Phagocytic and chemotaxis assays showed that rCcIL-15L could promoted the phagocytosis and chemotactic abilities of common carp HKLs. Our study provides a new perspective on the role for CcIL-15L in immunological functions in common carp.